Improving the hygiene of jamu sellers in Malang through the provision of appropriate technology - Nurwidodo , N.; Mulyono , M.; Fauzi, Ahmad (Journal of Community Service and Empowerment, 2021)
Jamu (herbal medicine) is included in traditional health drinks that its processing is often less hygienic. The purpose of this community service program is to improve the cleanliness of the herbal medicine-making process in the herbal medicine group in Malang through the provision of hygienic herbal medicine processing machines. Community service activities were carried out in 2018 by involving herbal medicine groups in Tegalgondo and Jetis Villages, Malang. The community service activities included analyzing the conditions and needs of partners, designing herbal medicine machines as needed, as well as assisting the use of machines. The implementation methods in this service program were discussion and training. The result of this service activity was an increase in partner knowledge regarding the importance of hygiene and the use of appropriate technology in herbal medicine processing. After the training was carried out, service partners began to be moved to process jamu more hygienically. Furthermore, assistance and technology-based marketing training activities also need to be carried out.